Thermal and Functional Group Analyses of Potato Starch and Corn Starch Biopolymer Film - Kabir, Mohamad Syahrul; Asman, Saliza (Enhanced Knowledge in Sciences and Technology, 2026)
Potato starch and corn starch are widely used to produce biopolymers because they contain amylose and amylopectin, the two main components responsible for polymer formation. In this study, potato and corn starch were used as raw materials to prepare biopolymers with glycerol added as a plasticizer to improve elasticity. Four biopolymer samples were prepared with different starch weights. A biopolymer sample was prepared from potato and corn starch at different starch contents were evaluated for their physical properties. The potato starch biopolymer with 2.0g showed the highest elasticity and transparency compared to the other samples. This difference is attributed to variations in the amylose and amylopectin content of each starch type. The thermal analysis results showed that the biopolymer sample with higher starch content has greater weight loss and lower thermal stability. Among the samples, potato starch biopolymers showed lower thermal stability compared to corn starch biopolymers, which may be attributed to their higher amylopectin content. The spectra of all samples showed similar functional groups, including C–O (1000–1300 cm⁻¹), C–H (700–900 cm⁻¹), C=O (1500–1800 cm⁻¹), C–H stretching (2800–3000 cm⁻¹), and O–H (3300–3500 cm⁻¹). The presence of the O–H group confirms amylose and amylopectin structures. The addition of glycerol introduced C=O groups associated with ester formation and slightly changed the intensity of certain peaks. These findings provide insight into how starch type and formulation composition influence the properties and stability of starch-based biopolymers, supporting their potential development as an environmentally friendly alternative material.